INFLUENCE OF HYDROPHOBITED ADDITIVES ON PHYSICAL AND MECHANICAL PROPERTIES OF CONCRETE IN AGGRESSIVE ENVIRONMENT - G'. M. Kadirov (Journals Park Publishing, 2022)
The article considers the influence of water-soluble salts on the thermophysical state of building envelopes. At various concentrations of salts, the protection of enclosing structures against changes in sorption and vapor permeability by damping was established
Keywords: closed constructions, types, properties, physical, chemical and biological processes, moisture, steam, salts, sorption processes, moisture condition, closed materials and pores.